Performance evaluation of primary care services for the treatment of tuberculosis - Silva, Daiane Medeiros da; Nogueira, Jordana de Almeida; Sá, Lenilde Duarte de; Wysocki, Anneliese Domingues; Scatena, Lucia Marina; Villa, Tereza Cristina Scatena (Revista da Escola de Enfermagem da USP, 2014)
Objective Evaluating the performance of primary care services for the treatment of tuberculosis according to the assessment referential of health services (structure/process) in Cabedelo, a port city in the state of Paraíba. Method An evaluation quantitative, cross-sectional study, in which were carried out 117 interviews with health professionals using a structured instrument. The analysis was based on the construction of indicators using a standardized value for the reduced variable (z=1). Results The structural indicators showed regular performance for the following variables: professional training, access to record instruments and coordination with other services. The process indicators related to external actions and information about the disease had unsatisfactory performance. The directly observed treatment and the flows of reference/counter-reference had regular performance. Conclusion The focused professional qualification, the fragmentation of practices and the unsystematic home care constitute obstacles for carrying out actions aimed at providing expanded, continuous and resolute care.